Capsaicin combined with ice stimulation improves swallowing function in patients with dysphagia after stroke: A randomised controlled trial. (19th August 2020) - Cui, Feifei; Yin, Qingmei; Wu, Chao; Shen, Meifen; Zhang, Yijie; Ma, Chen; Zhang, Haiying; Shen, Fang
Abstract: Background: Dysphagia is a common condition after stroke, and it is associated with many complications. Early and effective treatments are essential to the prognosis of patients with dysphagia. We aimed to evaluate the effects and safety of capsaicin combined with ice stimulation in patients with dysphagia after stroke. Methods: Patients with dysphagia admitted to our hospital from December 2017 to December 2019 were included. The control group received the ice stimulation, and the experimental group received the combined capsaicin and ice stimulation. The grade of water swallowing test (WST), standard swallowing assessment (SSA) scores and the serum substance P level was compared between control (ice only) and experimental group (capsaicin plus ice). Results: No differences before treatment and significance following treatment in each group (before and after) and between groups (capsaicin plus ice vs ice only) were found (all P  > .05); the SSA scores were significantly reduced after intervention for both groups (all P  < .001), and after intervention, SSA score in experimental group was significantly less than that of control group ( P  < .001). After intervention, the number of patients graded as WST level I‐II in experimental group was significantly more than that of control group ( P  < .001); the serum substance P level was significantly increased after intervention for both groups (all P  < .05), and after intervention, the serum substance P level in experimental group was significantly higher than that of control group ( P  = .007). Conclusions: The combined use of capsaicin with ice stimulation is beneficial to the recovery of swallowing function of patients with dysphagia, which should be included into the clinical practice.